Integration of Ethnoscience in the Development of a Problem-Based Learning–Based Science E-Module as a Contextual Learning Medium - Salwa Salwa; Mahrus Mahrus; Masayu Febiyanti; Kanaya Hasnah Al-Fadhilah (Indonesian Journal of Educational Innovation, 2026)
This study developed a Problem-Based Learning (PBL)-based science e-module integrating local ethnoscience from Lombok, Indonesia, and examined its validity, practicality, and effectiveness in improving students’ problem-solving skills and cognitive outcomes. Using the ADDIE model within a Research and Development (R&D) framework combined with a quasi-experimental design, four ethnoscience contexts of the Sasak community, traditional weaving dye techniques, Rinjani terraced irrigation, coastal salt production, and clay stove cooking, were systematically embedded as authentic problem scenarios across five PBL phases. Expert validation yielded a mean score of 90.1% (very valid). Student response surveys indicated 88.4% practicality. Pre-test and post-test analysis using N-gain showed a score of 0.63 (moderate-high) for the experimental group versus 0.35 for the control group, with a statistically significant difference (p < 0.001). Problem-solving skills improved across all four Polya indicators (N-gain 0.52–0.61). The ethnoscience-PBL e-module constitutes a contextually grounded digital learning medium that enhances scientific competence while valorizing indigenous cultural knowledge within the Merdeka Belajar curriculum.